Stimulation of chitin synthesis rescues Candida albicans from echinocandins. - Louise A Walker; Carol A Munro; Irene de Bruijn; Megan D Lenardon; Alastair McKinnon; Neil A R Gow (PLoS Pathogens)
Echinocandins are a new generation of novel antifungal agent that inhibit cell wall beta(1,3)-glucan synthesis and are normally cidal for the human pathogen Candida albicans. Treatment of C. albicans with low levels of echinocandins stimulated chitin synthase (CHS) gene expression, increased Chs activity, elevated chitin content and reduced efficacy of these drugs. Elevation of chitin synthesis was mediated via the PKC, HOG, and Ca(2+)-calcineurin signalling pathways. Stimulation of Chs2p and Chs8p by activators of these pathways enabled cells to survive otherwise lethal concentrations of echinocandins, even in the absence of Chs3p and the normally essential Chs1p, which synthesize the chitinous septal ring and primary septum of the fungus. Under such conditions, a novel proximally offset septum was synthesized that restored the capacity for cell division, sustained the viability of the cell, and abrogated morphological and growth defects associated with echinocandin treatment and the chs mutations. These findings anticipate potential resistance mechanisms to echinocandins. However, echinocandins and chitin synthase inhibitors synergized strongly, highlighting the potential for combination therapies with greatly enhanced cidal activity.